Pengaruh Penerapan Kurikulum Merdeka Belajar Terhadap Hasil Belajar Siswa di SMK Negeri 9 Padang pada Mata Pelajaran Pastry Bakery - Helinshia Zalukhu; Cici Andriani; Asmar Yulastri; Juliana Siregar (Lembaga Pengembangan Kinerja Dosen, 2025)
This research aims to analyze the effect of implementing the independent learning curriculum on student learning outcomes in the pastry bakery subject. The type of research used is quantitative with a simple random sampling data collection procedure with a sample of 70 students. The research was conducted at SMK Negeri 9 Padang on 12th grade students who had attended pastry bakery lessons, the research instrument used was a closed questionnaire by giving a google form questionnaire to the students. Data analysis using inferential analysis techniques used, namely the T test which is carried out with the statistical package for social science (SPSS) version 20.00. The results show that the influence of implementing the independent learning curriculum on student learning outcomes in the pastry bakery subject at SMK N 9 Padang, which teachers are expected to be able to develop all aspects of self-development to be independent in teaching in order to create independent learning for students.